2018
DOI: 10.1007/s00216-018-1264-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of odorous compounds in oak wood using odor extract dilution analysis and two-dimensional gas chromatography-mass spectrometry/olfactometry

Abstract: Over the centuries, oak wood has been used in the maturation process of alcoholic beverages imparting aroma and flavor notes. Whereas several studies have dealt with the impact of oak wood on the chemical composition of, for example, wine aroma, only limited information is available on the odorant composition of unmodified and raw oak wood itself. To close this gap, a combination of human sensory and chemo-analytical techniques was applied for the elucidation of the chemical composition of oak odor, comprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Besides the negative impact on color and bleachability, wood extractives are also responsible for the odor of the pulp [86]. Ghadiriasli et al [87] identified various volatile organic compounds (VOC), including terpenes https://doi.org/10.1007/s42452-021-04873-1 and degradation products from fatty acids and lignin, as odor-active compounds in oak wood, while Schreiner et al [88] stated more precisely that fatty acid degradation products represent about two third of all the odoractive compounds in pine wood. Among all fatty acid degradation products, aldehydes play an essential role as odor-active compounds because their odor threshold is very low, and their smell is generally considered highly unpleasant [12,89].…”
Section: Effects On Pulp and Paper Quality And Productionmentioning
confidence: 99%
“…Besides the negative impact on color and bleachability, wood extractives are also responsible for the odor of the pulp [86]. Ghadiriasli et al [87] identified various volatile organic compounds (VOC), including terpenes https://doi.org/10.1007/s42452-021-04873-1 and degradation products from fatty acids and lignin, as odor-active compounds in oak wood, while Schreiner et al [88] stated more precisely that fatty acid degradation products represent about two third of all the odoractive compounds in pine wood. Among all fatty acid degradation products, aldehydes play an essential role as odor-active compounds because their odor threshold is very low, and their smell is generally considered highly unpleasant [12,89].…”
Section: Effects On Pulp and Paper Quality And Productionmentioning
confidence: 99%
“…in Germany by gas chromatography-olfactometry (GC-O) and aromatic extract dilution analysis, identifying 44 types of odorous compounds. Ghadiriasli et al 14 found that the odor of oak wood mainly came from fatty acid degradation products, terpenoids, and lignin degradation based on GC-O and odor extraction dilution analysis technology. It was found that most odor components of oak were composed of a series of terpenoids, mainly monoterpenes and sesquiterpenes, aldehydes, acids and lactones, and some polyphenols containing phenolic core components.…”
mentioning
confidence: 99%
“…Smaller amounts of inorganic compounds and extractable substances, such as proteins, amino acids, fatty acids, terpenes, resin, acids, steroids, phenols, aldehydes, ketones, lactones and others are also present; it is in this group that we find the aroma compounds. Although there are many studies investigating the volatile composition of woods, few works concentrate on odour-active components [117,118,119].…”
Section: Woodmentioning
confidence: 99%
“…Schreiner et al [117,120] and Ghadiriasli et al [118], dedicated their studies to the identification of aromas in cedar incense ( Calocedrus decurrens (Torr.) Florin), Scots pine ( Pinus sylvestris L.) and oak wood ( Quercus frainetto ), respectively.…”
Section: Woodmentioning
confidence: 99%